Linking tonic and phasic pupil responses to P300 amplitude in an emotional face-word Stroop task - Chang, Yi Hsuan (2024)
The locus coeruleus-norepinephrine (LC-NE) system, which regulates arousal levels, is important for cognitive control, including emotional conflict resolution. Additionally, the LC-NE system is implicated in P300 generation. If the P300 is mediated by the LC-NE system, and considering the established correlations between LC activity and pupil dilation, P300 amplitude should correlate with task-evoked (phasic) pupil dilation on a trial-by-trial basis. However, prior studies, predominantly utilizing oddball-type paradigms, have not demonstrated correlations between concurrently recorded task-evoked pupil dilation and P300 responses. Using a recently developed emotional face-word Stroop task that links pupil dilation to the LC-NE system, here, we examined both intra- and inter-individual correlations between task-evoked pupil dilation and P300 amplitude. We found that lower accuracy, slower reaction times, and larger task-evoked pupil dilation were obtained in the incongruent compared to the congruent condition. Furthermore, we observed intra-individual correlations between task-evoked pupil dilation and P300 amplitude, with larger pupil dilation correlating with a greater P300 amplitude. In contrast, pupil dilation did not exhibit consistent correlations with N450 and N170 amplitudes. Baseline (tonic) pupil size also showed correlations with P300 and N170 amplitudes, with smaller pupil size corresponding to larger amplitude. Moreover, inter-individual differences in task-evoked pupil dilation between the congruent and incongruent conditions correlated with differences in reaction time and P300 amplitude, though these effects only approached significance. To summarize, our study provides evidence for a connection between task-evoked pupil dilation and P300 amplitude at the single-trial level, suggesting the involvement of the LC-NE system in P300 generation.